Priorities in Health Research (International Journal of Medical and Surgical Sciences, 2014)
The research process is dynamic and pragmatic, and that the results should be used for the generation of new knowledge. Moreover, research is part of academic activities; therefore, it has to take into account the results alsobecome input for teaching undergraduate and post graduate degree.